Kabuki syndrome: oral and general features seen in a 2-year-old Chinese boy - M. ATAR, W. LEE, & D. O’DONNELL (Paediatric Dentistry, 2006)
This report describes the case of a young Chinese boy with Kabuki syndrome (KS). KS is a congenital condition characterized by multiple anomalies, especially of the face, and is usually associated with mild to moderate mental retardation.